Water Quality, Mitigation Measures of Arsenic Contamination and Sustainable Rural Water Supply Options in Bangladesh - HOSSAIN M. ANAWAR; ZABED HOSSAIN; M. NUR HOSSAIN; SHAMIMA AKTER (International Journal of Economic and Environment Geology, 2012)
Arsenic contamination of groundwater has created a serious public health issue in Bangladesh and West Bengal (India), because groundwater is widely used for drinking, household and agriculture purposes. Given the magnitude of the problem of groundwater contamination facing Bangladesh, effective, acceptable and sustainable solutions are urgently required. Different NGOs (Non-government organizations) and research organizations are using their extensive rural networks to raise awareness and conduct pilot projects. The implication of the results from the previous studies is robust, but coastly arsenic reduction technologies such as activated alumina technology, and As and Fe removal filters may find little social acceptance, unless heavily subsidized. This review paper analysed the quality of surface water and ground water, all mitigation measures and the most acceptable options to provide sustainable access to safe- water supply in the rural ares of Bangladesh. Although there are abundant and different sources of surface water, they can not be used for drinking and hosehold purposes due to lack of sanitation, high faecal coliform concentration, turibidity and deterioration of quality of surface water sources. There are a few safe surface water options; and also there are several methods available for removal of arsenic and iron from groundwater in large conventional treatments plants. This review paper presented a short description of the currently available and most sustainable technologies for arsenic and iron removal, and alternative water supply options in the rural areas.